The Effect of Mckenzie Exercise to Increase Craniovertebral Angle in Forward Head Posture of Adolescent - Raras Hestina Laksmi; Nitaya Putri Nur Hidayati; Yuliana Ratmawati (Medica Hospitalia : Journal of Clinical Medicine, 2024)
BACKGROUND : adolescents with low physical activity and smartphone addiction has been indicated to reduced the craniovertebral angle, there by causing a forward head posture and increasing scapular dyskinesis, characterized by a craniovertebral angle (CVA) less than 50o. McKenzie is one of exercise that can helm correct posture in forward head posture AIMS : to determine the effect of the McKenzie exercise on increasing the craniovertebral angle in the forward head posture of adolescents. METHOD : students of MAN 1 Surakarta (Islamic Boarding School) with advanced head posture, aged 14-17 years using a simple random sampling technique divided into group I as the intervention group (n=16) and group II as the control group (n=14). Group I was given treatment of McKenzie exercise 3 times a week for 4 weeks, and the control group was not given any treatment. The Craniovertebral angle were assessed using photo analysis with Image-J application. RESULT : The results of the study indicate that the characteristics of respondents according to age are mostly 16 years old. The mean NDI score in the intervention group was 23,63 and the mean NDI score in the control group was 24,60. The results of statistical test using independent samples test showed that there was a significant difference during the intervention and the control group (p=0,000) CONCLUSION : McKenzie's exercise can affect to increasing the craniovertebral angle in the forward head posture of adolescents.